2009
DOI: 10.1039/b910549b
|View full text |Cite
|
Sign up to set email alerts
|

A mechanistic study of the low pressure pyrolysis of linear siloxanes

Abstract: Matrix isolation IR spectroscopy has been used to study the vacuum pyrolysis of 1,1,3,3-tetramethyldisiloxane (L1), 1,1,3,3,5,5-hexamethyltrisiloxane (L2) and 3H,5H-octamethyltetrasiloxane (L3) at ca. 1000 K in a flow reactor at low pressures. The hydrocarbons CH3, CH4, C2H2, C2H4, and C2H6 were observed as prominent pyrolysis products in all three systems, and amongst the weaker features are bands arising from the methylsilanes Me2SiH2 (for L1 and L2) and Me3SiH (for L3). The fundamental of SiO was also obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…Apparently, such a spectrum reflects a complex composition of the gas phase formed by a large number of molecules with various chemical bonds: Si-O-Si (1000-1100 cm −1 , Si-C-Si and Si-O-C (900-1100 cm −1 3 9 and Si-C in the range of 800 cm −1 . 23 The HMDSO pyrolysis study demonstrates [24][25][26] that the transformation begins with the siloxane bonds break with formation of a silyl radical and a silanone molecule:…”
Section: Resultsmentioning
confidence: 99%
“…Apparently, such a spectrum reflects a complex composition of the gas phase formed by a large number of molecules with various chemical bonds: Si-O-Si (1000-1100 cm −1 , Si-C-Si and Si-O-C (900-1100 cm −1 3 9 and Si-C in the range of 800 cm −1 . 23 The HMDSO pyrolysis study demonstrates [24][25][26] that the transformation begins with the siloxane bonds break with formation of a silyl radical and a silanone molecule:…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, many works, in particular those dealing with the polymer's industrial applications, suggest that polydimethylsiloxane‐based materials are well suited for foam control in food processing owing to their thermal stability and chemical inertness . On the other hand, various linear and cyclic PDMS have been reported to lead to thermal generation of the silicon analogue of acetone, that is, dimethylsilanone [(CH 3 ) 2 Si=O], which is believed to be an extremely reactive compound . Indeed, polydimethylsiloxane‐based silicon greases, which are believed to be chemically “inactive entities”, have been the subject of two review articles .…”
Section: Introductionmentioning
confidence: 99%
“…Several experimental studies have suggested that silanones are formed as intermediates in the thermal reactions of low‐molecular organosilicon compounds such as silylperoxides and hydrosilylperoxides, siloxetanes, silenes, hydridosilylketenes, allyloxysilanes, alkoxyvinylsilanes, and polysilylated diazomethanes . Linear and cyclic PDMS were reported to generate dimethylsilanone . These claims of dimethylsilanone formation were usually based on kinetic data and chemical trapping experiments .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations